Penatalaksanaan Nyeri Pasca Herniorafi dengan Blok Saraf Ilioinguinal dan Iliohipogastrik - Dzakwan Hakim Lubis; Aulianur Aulianur (Lembaga Pengembangan Kinerja Dosen, 2026)
Inguinal hernia is a common abdominal hernia occurring in the groin region and generally requires surgical management, with postoperative pain control being an important aspect of patient recovery. This case reports a 55-year-old male presenting with a left groin mass for 6 months, which was initially reducible but subsequently became difficult to reduce, accompanied by severe pain and activity limitation. Physical examination revealed a left inguinal mass measuring approximately 3.03 × 2.17 cm, with firm consistency, well-defined borders, immobility, and tenderness, while ultrasonography demonstrated dilation of the left inguinal canal after provocation; based on these findings, a diagnosis of left inguinal hernia with ASA physical status II was established. The patient was managed with herniorrhaphy under regional anesthesia using a subarachnoid block, followed by ultrasound-guided ilioinguinal and iliohypogastric nerve blocks with levobupivacaine and pehacain for postoperative analgesia. Intraoperatively, the patient remained hemodynamically stable, and postoperatively, pain intensity decreased gradually from a VAS score of 6 to 2 within 24 hours and reached 0 on the second postoperative day without significant complaints. This case demonstrates that regional anesthesia combined with ultrasound-guided peripheral nerve block may support postoperative pain control after herniorrhaphy, maintain clinical stability, and improve patient comfort during recovery.